Please Don't Wish Me a Merry Christmas : a Critical History of the Separation of Church and State. - Feldman, Stephen M., 1955- (Critical America., 1996)
Whether in the form of Christmas trees in town squares or prayer in school, fierce disputes over the separation of church and state have long bedeviled this country. Both decried and celebrated, this principle is considered by many, for right or wrong, a defining aspect of American national identity. Nearly all discussions regarding the role of religion in American life build on two dominant assumptions: first, the separation of church and state is a constitutional principle that promotes democracy and equally protects the religious freedom of all Americans, especially religious outgroups; and.